Immunogenicity and safety to SARS-Cov-2 vaccination in patients with systemic vasculitis - Biegelmeyer, Erika; de Freitas Aguiar, Mariana; Dias Cardoso Ribeiro, Priscila; Machado, Ketty Lysie Libardi Lira; Paiva França Telles, Camila Maria; Euzébio Ribeiro, Sandra Lúcia; Sarzi Sartori, Natália; Poubel Vieira de Rezende, Rodrigo; Guedes de Melo, Ana Karla; Alves Cruz, Vitor; Rodrigues de Abreu Vieira, Rejane Maria; Kakehasi, Adriana Maria; et al. (Frontiers in Immunology, 2025)
Background/objectivesPatients with systemic vasculitis faced the risk of severe COVID-19 and high mortality during the pandemic. Although SARS-CoV-2 vaccination mitigates these outcomes, vaccine hesitancy persists, and data on immunogenicity and safety in vasculitis is still limited. This study aims to assess response to primary and booster doses of SARS-CoV-2 vaccination in systemic vasculitis.MethodsThis multicenter cohort study including systemic vasculitis included patients from SAFER study (Safety and Efficacy of COVID-19 Vaccines in Rheumatic Diseases). We evaluated serum IgG levels against the SARS-CoV-2 spike protein receptor-binding domain (IgG anti-RBD) at baseline and 28 days post-vaccination, disease activity scores, new cases of COVID-19 infections, and adverse events.ResultsSeventy-three patients with systemic vasculitis were included. Behçet’s disease (n=39), Takayasu arteritis (n=15), and antineutrophil cytoplasmic antibody-associated vasculitis (n=14) were the most common vasculitis forms. The majority of the patients had no comorbidities and were in remission. Seventy patients received one, 65 two, and 60 three vaccine doses. ChAdOx1 nCoV-19 (AstraZeneca/Oxford) (n=36) and CoronaVac (Sinovac) (n=25) were primarily the most common vaccines, while BNT162b2 (Pfizer–BioNTech) was usually the booster vaccine. ChAdOx1 nCoV-19 induced higher IgG anti-RBD than CoronaVac after two doses (p=0.002), but this difference disappeared after the booster dose. No differences in vaccine response were noted between heterologous and homologous regimens or vasculitis types. The new cases of COVID-19 (16.9%), hospitalization (1.5%), and mortality (1.5%) rates were relatively low following vaccination. Disease activity remained stable, and adverse events were mostly mild. Only one severe adverse event was observed.ConclusionDifferent SARS-CoV-2 vaccines demonstrated immunogenicity and clinical effectiveness in systemic vasculitis. The three-dose schedule was safe without increasing relapse risk.